STUDI ANTIDIABETES KOMBINASI EKSTRAK ETANOL KUBIS (Brassica oleracea L.) DAN TOMAT (Solanum lycopersicum L.) SECARA IN VITRO - Devina Ingrid Anggraini; Dwi Damayanti (Fakultas Farmasi UMI, 2019)
Diabetes mellitus is a health problem in the world including Indonesia. A lot of treatment efforts to control and lowering blood sugar levels done with drugs hypoglycemic of natural materials. This research was conduct to determine the combination of extract cabbage (Brassica oleracea L.) and tomato (Solanum lycopersicum L.) have activity antidiabetic and more effective than extract single. Study performed on four comparison concentration sample extract ethanol cabbage and tomato are 1: 0; 2: 1; 1: 2 and 0: 1. Method wich is use in this study the method of Nelson-Somogyi by using the instrument spectrophotometer UV-Vis. Decline glucose levels highest obtained in the concentration of extract cabbage and tomato with the ratio of 1: 2 is 4,5165 ppm and decrease in glucose levels lowest obtained in the concentration of extract cabbage and tomato with the ratio of 1: 0 is 5,1613 ppm.